The diversity and distribution of chigger mites associated with rodents in the South African savanna. Issue 9 (4th August 2020) - Matthee, Sonja; Stekolnikov, Alexandr A.; van der Mescht, Luther; Froeschke, Götz; Morand, Serge
Abstract: Chigger mites (Trombiculidae) are temporary habitat-specific ectoparasites that often occur on rodents. Little ecological data are available on chiggers associated with rodents in South Africa. The study aims were to (1) record the chigger species associated with rodents in the savanna, (2) assess if chigger species display parasitope preference on the rodent body and (3) compare the distribution of chigger species in natural, agricultural and urban habitats. Rodents ( n = 314) belonging to eight genera were trapped in the savanna biome during 2014 and 2015. Twelve chigger species, of which five are recently described species, were recorded from 161 rodent hosts. The data include three new country locality records. Microtrombicula mastomyia was the most prevalent species across sampling seasons and habitat types. Significant parasitope preference was recorded for two species, with the ear, face and tail base some of the preferred attachment sites. Sampling season and habitat type had a significant effect on chigger communities with summer and agricultural habitats recording the highest species richness, while the highest species diversity was recorded in natural habitats. The study contributes to our current knowledge regarding rodent-associated chigger diversity and distribution in South Africa and further highlights the importance of environmental characteristics in shaping chigger communities.